Implementation of Horse Care Training in the Tourism Village of Ngestirejo Tanjungsari Gunungkidul - Yudan Hermawan; Sugito Sugito; Tristanti Tristanti; Adin Ariyanti Dewi (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2022)
This study aims to get an overview of how the Horse Care Training process in the Tourism Village of Ngestirejo, Tanjungsari District, Gunungkidul Regency, using a qualitative approach through the case study method. Data collection techniques were carried out in this study using observation, interviews and documentation related to training activities. The data analysis stage in this study uses three steps, including: 1) data condensation, 2) data display, and 3) conclusion drawing and verification. While the validity of the data in this study using triangulation techniques and persistence in field observations. This study shows that implementation is carried out in five stages; 1) Determination of needs, 2) determination of targets, 3) Determination of Training Materials, 4) implementation of the program and 5) Evaluation of Program Implementation. Outcomes of the Training: 1) The trainees understand and know how to properly care for horses. 2) The trainees know the stages of guiding and riding a horse as a tour. 3) The trainees are motivated and have high enthusiasm in participating in the training.Keywords: implementation, training, horse care, tourist village